Musculocutaneous Neuropathy Following Insertion of Cosmetic Silicone Biceps Implants: A Case Report. (September 2015) - Simon, Jeremy; McAuliffe, Matthew; Vuong, Nancy; Armstrong, Joshua; Beredjiklian, Pedro K.
This is a case report of a 40-year-old man who underwent bilateral cosmetic biceps implantation, developed pain, and had the implants removed. He then developed weakness and numbness in the left arm and was subsequently found to have musculocutaneous neuropathy by electromyography and ultrasound. After failing to respond to conservative care and having ongoing weakness, the patient underwent a neurolysis and debridement of the musculocutaneous nerve. Subsequently, he regained full function and use of the left upper limb. This case report brings attention to musculocutaneous neuropathy as a potential complication of cosmetic bicipital implantation surgery.